My little pony, friendship is magic. Spring into friendship [videorecording (DVD)] (My little pony: friendship is magic., 2018)
It's time to Spring into friendship with five exciting pony adventures. When Twilight Sparkle has two tickets to the Grand Galaping Gala, she has to decide which of her pony pals should go with her. And young filly Apple Bloom makes some very special friends to help her discover her cutie mark. During an important celebration in Equestria, Twilight and her friends must work together when Princess Luna and Princess Celestia go missing.